Prevalência de anemia em pré-escolares atendidos na rede municipal de Maringá, Paraná - Veloso, Giovanna Batista Leite (2007)
Anemia caused by iron deficiency is an illness that occurs frequently all over the world, reaching mainly children in preschool and pregnant women. In Brazil this is a problem that has great proportions when compared with other deficiencies and it is known that it is caused by an inadequate feeding, usually poor in iron content. For that reason the government enforced the Resolution n. 344 of December 13, 2002, that established the enrichment of wheat and corn flour, in an attempt to decrease the anemia indexes, once great number of the population makes use of that kind of food. The objective of this study was to estimate the prevalence of anemia in preschool children assisted in the municipal schools of Maringá, Paraná before and after the enrichment of the wheat and corn flour with iron. The study was carried out with 403 children at preschool age of the municipal district of Maringá, enrolled in the Municipal Centers of Child Education in the year of 2006. To check the anemia index, the results of hemoglobin exams were verified in the children's medical records at the Health Units where each child was attended. The anemia prevalence found in this population was compared to a study carried out before the flour enrichment. Epidemic variables were also collected to verify its relationship with the presence of anemia. These variables were obtained through the children's medical records and at SINASC of the 15th Regional of Health of Paraná. Through this study it was observed that there was a significant improvement after the implantation of the program. The anemia prevalence that was of 31.74% decreased to 20.35%, with coefficient of variation of 35.88% (p=<0.005). The variables that proved relationship with the anemia were the child's age under 2, and malnutrition. The other variables indicative of the child's characteristics, birth, gestation and the mothers' socioeconomic conditions, showed no relationship with the anemia presence, although they are very important in the genesis of the iron deficiency anemia. Data obtained in this study demonstrate the positive impact that the implantation of the Program of enrichment of wheat flour and corn caused on the anemia control, and also the importance of afollow-up of the age risk groups on the development of such deficiency aiming at its prevention and control.